Comparative digestibility studies with hens and rats - Syrjälä, Liisa (Agricultural and Food Science, 1971)
Trials were made to compare the digestibility of feeds in hens and rats. In the comparison particular attention was paid to the true digestibility of the feeds. The digestibility of rusks made of wholewheat meal was compared in hens and rats. The rats digested 62.1 % of the cell wall substances of the whole wheat meal, while the value for the hens was 16 %-units lower. The true digestibility of the other N-free organic matter was also clearly lower in the hen trial than in the rat trial. In the rat trials the digestibility of wholewheat meal was compared with that of bark meal. The true digestibility of the organic matter of the bark meal was only 23.6 %, while that of the wholewheat meal was 92.4 %. The digestibility of the cell wall substances of the bark meal was 18.5 % and of the wholewheat meal 62.1 %.